Meat Consumption and Gut Microbiota: A Scoping Review of Literature and Systematic Review of Randomized Controlled Trials in Adults Without Diagnosed Disease. (14th June 2022) - Wang, Yu; Uffelman, Cassi; Bergia, Robert; Clark, Caroline; Reed, Jason; Cross, Tzu-Wen; Lindemann, Stephen; Tang, Minghua; Campbell, Wayne
Abstract: Objectives: Meat is an important dietary component for the majority of the U.S. population. Emerging research indicates the importance of gut microbiota in mediating the relationship between meat intake and human health outcomes. We aim to assess the state of available scientific literature on meat intake and gut microbiota in humans. Methods: We first conducted a scoping review to identify observational and interventional studies on this topic. Based on findings from the scoping review, we conducted a systematic review using suitable literature to assess the influence of meat intake on gut microbiota. Searches were performed for English language articles using PubMed, Cochrane Library, Scopus, and CINAHL databases from inception to August 2021, and keywords related to meat (inclusive of mammalian, avian, and aquatic subtypes) and gut microbiota. Results: Of 14, 680 records, 84 eligible articles were included in the scoping review, including 57 observational and 27 interventional studies. One prospective observational study and 13 randomized-controlled trials (RCTs) were identified in adults without diagnosed disease. We included the 13 RCTs, comprising 18 comparisons, in the systematic review to assess the effects of higher versus lower intakes of total meat and meat subtypes on gut microbiota composition. Collectively, meat intake differentially affected bacterial composition more frequently at lower taxonomic levels (genus or species) than higher taxonomic (phylum or class) or community structure (alpha diversity) levels. A similar hierarchical pattern of findings was observed when higher versus lower meat intakes (12 comparisons) or omnivorous versus vegetarian-style diets (7 comparisons) were assessed. Yet, the directionality and types of microbial responses varied, with no consistent pattern of responses across studies in bacterial taxa. The data were insufficient for comparison within or between meat subtypes. Conclusions: The paucity of research, especially among meat subtypes, and heterogeneity of findings underscore the need for more well-designed prospective studies and full-feeding randomized-controlled trials to address the relationships between and effects of, respectively, consuming total meat and meat subtypes on gut microbiota. Funding Sources: Beef Checkoff.